Five new polyketides from the basidiomycete Craterellus odoratus - Guo, Hua (Springer Berlin Heidelberg, 2012)
Five new polyketides, craterellones A–E (1–5), were isolated from cultures of basidiomycete Craterellus odoratus, together with five known compounds (6–10). Structures of 1–5 were elucidated on the basis of extensive spectroscopic analysis. All compounds were evaluated for their inhibitory activities against one isozyme of 11β-hydroxysteroid dehydrogenase (11β-HSD1) and cytotoxic activities on five tumor cell lines. Compound 10 exhibited significant cytotoxicity against HL-60, SMMC-7721, A-549, MCF-7, and SW-480, with IC50 values of 0.50, 0.69, 0.64, 1.10, 0.54 µM, respectively. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-012-0057-5 and is accessible for authorized users.